2002
DOI: 10.1063/1.1473234
|View full text |Cite
|
Sign up to set email alerts
|

Organic electrical bistable devices and rewritable memory cells

Abstract: Electrical bistability is a phenomenon in which a device exhibits two states of different conductivities, at the same applied voltage. We report an organic electrical bistable device (OBD) comprising of a thin metal layer embedded within the organic material, as the active medium [L. P. Ma, J. Liu, and Y. Yang, US Patent Pending, (2001)]. The performance of this device makes it attractive for memory-cell type of applications. The two states of the OBD differ in their conductivity by several orders in magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
293
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 484 publications
(307 citation statements)
references
References 11 publications
(16 reference statements)
8
293
1
5
Order By: Relevance
“…Ma et al first demonstrated that resistive switching could be achieved by depositing a layer of aluminum nanoparticles between two organic layers. 3 Because the depositions of the nanoparticles and the organic layer are independently controlled, the distribution of nanoparticles can be very well controlled in these devices. Figure 1 shows a typical structure for such devices.…”
Section: Device Structure and Fabrication Of The Nonvolatile Memory Dmentioning
confidence: 99%
See 3 more Smart Citations
“…Ma et al first demonstrated that resistive switching could be achieved by depositing a layer of aluminum nanoparticles between two organic layers. 3 Because the depositions of the nanoparticles and the organic layer are independently controlled, the distribution of nanoparticles can be very well controlled in these devices. Figure 1 shows a typical structure for such devices.…”
Section: Device Structure and Fabrication Of The Nonvolatile Memory Dmentioning
confidence: 99%
“…Obviously, for practical applications, a high switching speed (o100 ns) is necessary to meet the requirement of ultra-high-density information storage. Ma et al 3 reported that a hybrid memory cell could exhibit a switching speed as fast as 10 ns.…”
Section: Electrical Memory Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymer memory devices show fast switching speed and non-volatile characteristics (Ma et al 2002;Ouyang et al 2004;Scott & Bozano 2007), and are therefore ideal candidates to replace existing memory technologies. However, in order for polymer memory to achieve commercial success, there are a few hurdles that need to be overcome.…”
Section: Introductionmentioning
confidence: 99%